2022
DOI: 10.3390/ijms23062905
|View full text |Cite
|
Sign up to set email alerts
|

The Sleep-Promoting Ventrolateral Preoptic Nucleus: What Have We Learned over the Past 25 Years?

Abstract: For over a century, the role of the preoptic hypothalamus and adjacent basal forebrain in sleep–wake regulation has been recognized. However, for years, the identity and location of sleep- and wake-promoting neurons in this region remained largely unresolved. Twenty-five years ago, Saper and colleagues uncovered a small collection of sleep-active neurons in the ventrolateral preoptic nucleus (VLPO) of the preoptic hypothalamus, and since this seminal discovery the VLPO has been intensively investigated by labs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 130 publications
0
20
0
Order By: Relevance
“…Two galanin-expressing populations are present in the VLPO nucleus: the VLPO “core” or “cluster,” thought to promote non–rapid eye movement (non-REM) sleep, and the “extended” VLPO nucleus linked to the regulation of REM sleep 11 . The precise location of a human homologue of the rodent VLPO nucleus remains uncertain.…”
Section: Fundamentals Of Sleep and Wakefulnessmentioning
confidence: 99%
See 1 more Smart Citation
“…Two galanin-expressing populations are present in the VLPO nucleus: the VLPO “core” or “cluster,” thought to promote non–rapid eye movement (non-REM) sleep, and the “extended” VLPO nucleus linked to the regulation of REM sleep 11 . The precise location of a human homologue of the rodent VLPO nucleus remains uncertain.…”
Section: Fundamentals Of Sleep and Wakefulnessmentioning
confidence: 99%
“…10 Two galanin-expressing populations are present in the VLPO nucleus: the VLPO "core" or "cluster," thought to promote non-rapid eye movement (non-REM) sleep, and the "extended" VLPO nucleus linked to the regulation of REM sleep. 11 The precise location of a human homologue of the rodent VLPO nucleus remains uncertain. Neurons in the hypothalamic intermediate nucleus have similarities to the rodent VLPO nucleus, including their location in the chiasmatic region and the expression of galanin.…”
Section: Fundamentals Of Sleep and Wakefulnessmentioning
confidence: 99%
“…As a key arousal node, the LC receives inputs from arousal-related neurons and provides widespread NEergic innervation to the cerebral cortex and other forebrain structures related to anesthesia and sleep, such as the VLPO. The VLPO is important for sleep generation and contains multiple neuronal populations including GABAergic and galaninergic neurons, which are thought to be sleep-active neurons 28 .…”
Section: Discussionmentioning
confidence: 99%
“…As a key arousal node, the LC receives inputs from arousal-related neurons and provides widespread NEergic innervation to the cerebral cortex and other forebrain structures related to anesthesia and sleep, such as the VLPO. The VLPO is important for sleep generation and contains multiple neuronal populations including GABAergic and galaninergic neurons, which are thought to be sleep-active neurons 28 . Previous studies revealed the effect of the LC to VLPO pathway regulation of arousal and found that LC NE neurons synergistically promote arousal by activating wake-active neurons and inhibiting sleep-active neurons in the VLPO simultaneously 21 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cholinergic neurons in the pedunculopontine nucleus, laterodorsal tegmental nucleus, and glutamatergic neurons in the parabrachial nucleus promote wakefulness. [8] The structures that promote sleep mainly include the ventrolateral preoptic nucleus [9] and the middle preoptic nucleus [10] of the hypothalamus, which are excited during sleep and the pineal gland that produces melatonin. [11] Therefore, the main neurons that regulate sleep arousal are located in the brainstem and hypothalamus.…”
Section: Discussionmentioning
confidence: 99%